Corporate citizenship-plowing back profits to the community (Vision Creation Corporation) - Andaya, Eric A. (School of Management, UP Mindanao, 2003)
Vision Creation Corporation has just entered its 6th year of operation, coming from the initial plan adapted from its parent organization VCC hopes to devise its own Strategic plan to address the issues it is faced towards the future. The Amusement Industry in the Philippines is relatively not young anymore. Having started in 1987, a lot of amusement operators have sprouted trying to venture into this profitable business. VCC being an offshoot of the Internationally known Tom?s World and Paco Group of Companies started operations only just recently and is currently moving to pursue a modified Vision and Mission towards the coming years. It is with this plan that Vision Creation Corporation hopes to formulate and follow a company strategy for the next six years that is attuned to meeting the company's Vision and Mission with an end result of achieving competitive advantage subsequently justifying the amusement firm?s existence. Data for this paper was gathered using company documents and interviews from the Chairman of the Board, the Executive Director of VCC, VCC General Manager, Department Heads and significant employees as the main source and Focus Group Interviews, academic references and Internet web sites as secondary sources. Using Thompson and Strickland framework a complete evaluation done arriving at strategies suited for the current strategic issues VCC is faced with. A careful analysis of the External factors placed emphasis on societal, political, regulatory, and community citizenship considerations, the industry's competitive conditions, and the company's opportunities and threats. Following the framework an internal analysis was also conducted, and this focused mainly on VCC's Strengths, weaknesses, and its competitive capabilities. Also a discussion on VCC's culture, which is tied to an age-old tradition adapted from its foreign counterparts and other local amusement operators was incorporated. This despite existence of Core Values like: results and profit oriented, teamwork, accountability, working hard and working smart, sense of ownership, people development and continuous learning, and social responsiveness and responsibility. From here, a matching of the strengths and weaknesses was conducted, thus identifying strategic issues. This issues were identified as the following: emerging resistance from families and the Philippines government, operational profitability and opportunity for growth and expansion, high cost of investment and high cost of maintenance, corporate culture that is tied to age old tradition, high threat of entry and easy and strong influence for substitutes. This paper focuses mainly on three strategies, organizational restructure and decentralization, growth and expansion and corporate social responsibility. In order for VCC to pursue an intensive expansion strategy and eventually break free from the age old culture and traditions, restructuring and decentralization will be pursued on the initial year. This will pave the way for the establishment of autonomous Profit Center teams that will help counteract the expanding and widening span of control, as well as be more adaptive to the current and new environment VCC will be facing. Simultaneously VCC will venture into an expansion program that will target the opening of thirty three (33) new locations covering the span of six years. Through this strategy, VCC will solidify its position in the amusement industry focusing more on provincial locations and eventually becoming one of the most dominant forces in the industry. The growth and expansion will also be targeted to yield a net profit margin of an average 31.56 percent with a constant annual increase of twenty percent from gross sales starting 2003. Together, VCC hopes to strengthen one of its core values through the implementation of a Corporate Social Responsibility strategy. Through the emerging resistance being exhibited not only by families as well as the Philippine government highlighted by documentaries showing video games having unfavorable results to the children ? which is the primary target market of VCC ? the CSR strategy will help alleviate such burden. This will promote goodwill, and enhance the company's reputation and standing in the society. Implementing guidelines were placed at the latter part to facilitate accomplishment of this strategic plan. Through this plan, VCC hopes to achieve to plow back profits back into the society were views towards an amusement industry is faced with an emerging resistance.